EVALUASI MANFAAT PROGRAM JAMINAN KESEHATAN DAERAH BAGI MASYARAKAT KOTA YOGYAKARTA - , ROHADANTI; , dr Sigit Riyarto, M. Kes ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: The Program of Community Health Insurance Scheme (Jamkesda) in the city of Yogyakarta organized by the Technical Unit Regional Health Insurance Provider (UPT PJKD) with funds from the city budget. Rule about membership, benefits and amount of Jamkesda was appointed in the Mayor Regulation. There has been no comprehensive research about benefits and the perceived difficulty when using Jamkesda. This research aims to find it. Methods: This research is an observational study by using quantitative and qualitative methods. Quantitative respondents (n = 154) selected by accidental when the patient is being treated at two hospitals in Yogyakarta and is based on the recapitulation of the claims in the previous month. Qualitative respondents (n = 10) selected by purposive sampling in which patients with chronic illnesses and who have very high claims. Data collection was taken by questionnaire and guideline for in-depth interviews to participants Jamkesda who has been treated in two hospitals. Results: Respondents felt Jamkesda benefits despite objecting to 51.30% of the cost sharing, so that in-depth interviews five informants expressed borrow to pay for it. 61.04% of respondents use a letter of recommendation from Department of Social, Labor and Transmigration (people who have no health insurance). Difficulty in handling the identity of membership is only experienced by 16.23%, while 78.57% felt easy in use. Peoples who find difficulty are looking for a solution to the government administrator as RT/RW, parliamentarians, NGOs and neighbors. There is 78.57% of respondents did not understand about the limits service of Jamkesda, their only knows information relating to their current interests. 89.61% of respondents knew that Jamkesda are helps them. There are 73.38% and all the respondents who were interviewed paid the cost sharing more than 10% of total claims. From the total household expenditure, almost all (99,35